Enhancing household food security through soil and water conservation practices: a case study in semi-arid areas of Ethiopia - Ayalew, M. W.; Teferi, E. T.; Wassie, S. B.; Mhiret, D. A.; Aakle, A. T.; Dagnew, D. C.; Adem, A. A.; Tilahun, Seifu A. (Elsevier, 2025)
Over recent decades, Ethiopia has substantially invested in soil and water conservation (SWC) practices, particularly in arid areas to strengthen environmental resilience, maintain agricultural productivity, and improve food security. Despite huge efforts, the impact of practices on improving households’ food security remains unexplored. This study, therefore, examines the impact of SWC practices on households’ food security in the semi-arid areas in Northwestern Ethiopia. The data collected from 546 households was analyzed using an endogenous switching regression (ESR). The findings showed that 52% of the surveyed households implemented SWC practices such as soil bunding, stone bunding, stone-faced soil bunding, and terracing on their farmlands. Adopters of SWC practices consumed more diversified foods with a higher dietary diversity score of 7.3 points and food consumption scores of 18.7 points compared with 0.63 and 4.02 points respectively for non-adopters. Adopters also reported lower scores on the Food Security Scale and Food Insecurity Experience Scale. The results suggest that adopting SWC practices improves utilization and stable access to food through enhancing soil fertility and restoring degraded farmlands to sustain existing and new food and fodder crops. This has led to an improved farm-level productivity and increased production diversity thereby contributing to household-level food security. The overall findings underscore the positive impact of SWC interventions on food security outcomes among adopter households in semi-arid areas of Ethiopia. However, the heterogeneity in treatment effects suggest that policymakers, extension agents, and local agricultural offices should consider individual and context specific conditions to effectively promote scaling SWC practices.